Addressing diaper need as racial stratification through intersectional family justice. Issue 5 (21st May 2022) - Randles, Jennifer
Abstract: Objective: To use racial stratification and intersectional family justice frameworks to analyze experiences of and efforts to address diaper need. Background: One in three American families with infants and toddlers struggles with insufficient access to diapers, which can have negative social, physical, and economic implications for family well‐being. Prior research has yet to examine diaper need as a form of racial stratification, despite existing evidence of racialized prevalence. Method: In‐depth interviews were conducted with nonrandom samples of 70 mothers who experienced diaper need, including 61 mothers of color, and 40 diaper bank advocates. Qualitative abductive coding techniques were employed to identify how diaper need is experienced and framed as a form of racial stratification. Results: Mothers of color were more likely to report racialized stigma, stress, surveillance, and social exclusion associated with diaper need. Diaper bank advocates framed diaper assistance as necessary to address intersecting race, class, and gender inequalities of diaper distress. Conclusion: Conceptualizing diaper need and public responses as issues of racial stratification and intersectional family justice points to how family scholarship can center analyses of systemic oppression and privilege to optimize family and caregiving relationships and promote equitable pathways to well‐being for all families. Implications: These findings reinforce the importance of racially just strategies for equalizing access to basic needs and caregiving resources in ways that account for the racist underpinnings of social problems like diaper need and related influences on parenting experiences.